Cyber Espionage Real Threat to Banking - Priyanka Gowda Ashwath Narayana Gowda (North American Journal of Engineering Research, 2024)
Cyber espionage poses a significant risk to the banking industry since the data is stolen secretly for political or economic reasons. Banks are among the most vulnerable, as they deal with millions of people and substantial amounts of money together with personal data. Successful cyber and hacktivism attacks can lead to enormous financial losses, unauthorized access to sensitive data, penalties, and damage to organizational reputation and operations interfering with the financial value chain. It becomes important to contain cyber espionage in so far as the stability of the banking sectors is concerned. Banks have to develop extensive cybersecurity measures that comprise a further level of threat identification, personnel’s awareness, and integration with other credit institutions and authorities. Security testing and threats intelligence are some of the strategies that can be taken to avoid such risks. In this case, by focusing on cybersecurity, the banks will be able to safeguard their processes and hence retain their consumers’ confidence. Therefore, in the technological and collaborative aspects, banking sector is capable of safeguarding itself against such cyber espionage, and in turn the stability of the financial services